Employment Verification Mandates and the Labor Market Outcomes of Likely Unauthorized and Native Workers - Catalina Amuedo-Dorantes; Cynthia Bansak (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2013)
As recent efforts to reform immigration policy at the federal level have failed, states have started to take immigration matters into their own hands and researchers have been paying closer attention to state dynamics surrounding immigration policy. Yet, to this date, there is not a clear understanding of the consequences of enforcing E-verify on likely unauthorized immigrants and on native-born workers across the United States. This study aims to fill in that gap by analyzing the impact that the enactment of various types of E-verify mandates may have on the employment and wages of these two populations. We find that the enactment of both universal and public-sector only mandates reduce employment of likely unauthorized workers. Meanwhile, employment verification does not affect naturalized Hispanic workers but increases the employment likelihood of native workers. Impacts on wages are positive for likely unauthorized women suggesting a large labor supply reduction. For native-born workers, hourly wages also increase and provide some evidence of substitutability of unauthorized immigrants and non-Hispanic natives.
Keywords: J2; J3; J6; 330; E-Verify; Undocumented Workers; Employment; Wages